Avaliação da toxicidade e degradação de M. aeruginosa e Microcistina-LR por AOPs e nanopartículas de prata - Müller, Luciana (2017)
Cyanobacterial blooms are easily found, due to the increasing nutrient supply in natural and artificial bodies of water, caused by the accelerated processes of eutrophication, fruits of urban and rural occupation without observing minimum criteria. Microcystis aeruginosa is a specie of cyanobacteria that are potentially cyanotoxin-producing, commonly associated with cases of worldwide intoxication. New technologies for water treatment have been implemented to meet the standards of potability required by legislation. The present study looked for analyze the world scientific production related to the treatment of water with presence of M. aeruginosa and MC-LR, seeking to identify the state of the art, besides supporting the discussion of the proposed methods. The present study is divided into three articles, the first one was a bibliometric analysis of the world-wide research related to cyanobacteria, cyanotoxins and water treatment, from the Scopus database. In the second article evaluated the aplicability of UV-C e UV-C/H2O2 AOPs on degradation of Microcystis aeruginosa BB005 and MC-LR, and the analysis of effects Ag nanoparticles addition, based on a commercial product composed of hydrogen peroxide (H2O2) and silver nanoparticles (NAg). In the trird article evaluated the water quality produced, from acute toxicity tests with Daphnia magna. The results indicate that photolysis and the UV-C/H2O2 process presents satisfactory results, being an efficient alternative. However, the results of the ecotoxicity assays infer that these treatments used for the purpose of degrading M. aeruginosa and MCLR, have potential to generate toxic degradation byproducts: the D. magna assays demonstrated toxicity even when the water submitted to photolysis was diluted four times. Regarding the UV-C/H2O2 process (without and with NAg addition), the sample was toxic when undiluted. When NAg was used in combination with UV-C radiation, it showed extremely high toxicity, affecting the mobility of all test organisms at all dilutions (until 16x).